The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1970
DOI: 10.1246/bcsj.43.3453
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Impurities upon the Physical Properties of Silica Gel by the Heat-Treatment

Abstract: The effects of various kinds of inorganic salts upon the physical properties of silica gel heated in the range up to 1200°C were studied. We measured the polymorphic behavior by means of X-ray diffraction, the simultaneous measurement of the differential thermal analysis, and the thermogravimetric analysis, and the specific surface area by means of the BET N2 method and by means of studying the water-adsorption capacity. The cationic impurities which were found to have strong effects upon the physical properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1973
1973
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 3 publications
1
7
0
Order By: Relevance
“…Crystallization rates for 100 h at 1000°C and 10 h at 1100°C are comparable to some rates found in the literature, albeit with more tridymite formation than cristobalite . Presence of impurities, particularly sodium, is often suggested to promote tridymite crystallization over that of cristobalite, but the literature is inconsistent on this; some studies are ambiguous or suggest that sodium promotes cristobalite crystallization . Both higher and much lower crystallization temperatures were reported for oxide scales formed on a single crystal and CVD (β) SiC.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…Crystallization rates for 100 h at 1000°C and 10 h at 1100°C are comparable to some rates found in the literature, albeit with more tridymite formation than cristobalite . Presence of impurities, particularly sodium, is often suggested to promote tridymite crystallization over that of cristobalite, but the literature is inconsistent on this; some studies are ambiguous or suggest that sodium promotes cristobalite crystallization . Both higher and much lower crystallization temperatures were reported for oxide scales formed on a single crystal and CVD (β) SiC.…”
Section: Resultssupporting
confidence: 68%
“…3,72 Presence of impurities, particularly sodium, is often suggested to promote tridymite crystallization over that of cristobalite, 3,5,11,73 but the literature is inconsistent on this; some studies are ambiguous or suggest that sodium promotes cristobalite crystallization. [74][75][76] Both higher 21 and much lower 20 crystallization temperatures were reported for oxide scales formed on a single crystal and CVD (b) SiC. Neither study reported the type of furnace tube that was used, or other details helpful in assessment of the possible role of impurities.…”
Section: November 2011mentioning
confidence: 99%
“…The available literature data show that the change in silica structure from the amorphous to the crystal state occurs at a temperature of 1000 • C [9][10][11]. Kondo et al [9,10] studied the influence of impurities and pH of the solution on the structure change of thermally treated silica gel.…”
Section: Resultsmentioning
confidence: 99%
“…Kondo et al [9,10] studied the influence of impurities and pH of the solution on the structure change of thermally treated silica gel. They concluded that the amorphous to crystal structure change depends on the type and concentration of cations and is independent of the type of anions present as impurities.…”
Section: Resultsmentioning
confidence: 99%
“…The cross-section TEM micrograph of S-500O1000N sample ͓Fig. 30,31 No crystalline features have been observed by the selected area electron diffraction analysis in agreement with the GIXRD pattern ͓Fig.…”
Section: Tem and Gixrdmentioning
confidence: 59%